Amoxicillin-Clavulanic Acid Empirical Oral Therapy for the Management of Children with Acute Haematogenous Osteomyelitis - Elena Serrano; Irene Ferri; Luisa Galli; Elena Chiappini (MDPI AG, 2020)
According to the Guidelines of the European Society of Pediatric Infectious Diseases (ESPID), in low methicillin-resistant Staphylococcus aureus (MRSA) prevalence settings, short intravenous therapy is recommended in uncomplicated cases of acute haematogenous osteomyelitis (AHOM), followed by empirical oral therapy, preferentially with first/second-generation cephalosporin or dicloxacillin or flucloxacillin. However, several practical issues may arise using some of the first-line antibiotics such as poor palatability or adherence problems. Clinical, laboratory and therapeutic data from children with AHOM hospitalized in one Italian Paediatric Hospital between 2010 and 2019 were retrospectively collected and analyzed. The aim of the study was to highlight the extent of the use and the possible role of amoxicillin-clavulanic acid in the oral treatment of children with AHOM. Two hundred and ten children were included. S.aureus was identified in 42/58 children (72.4% of identified bacteria); 2/42 S.aureus isolates were MRSA (4.8%). No Kingella kingae was identified. Amoxicillin-clavulanic acid was the most commonly used oral drug (60.1%; n = 107/178) and it was associated with clinical cure in all treated children. Overall, four children developed sequelae. One (0.9%) sequela occurred among the 107 children treated with amoxicillin-clavulanic acid. Our results suggest that amoxicillin-clavulanic acid might be an option for oral antibiotic therapy in children with AHOM.